2015
DOI: 10.14306/renhyd.19.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a rapid method for detecting nitrate in chard (Beta vulgaris cycla). Analysis of Spanish commercial samples marketed in the Region of Huesca, Spain, and estimation of the daily intake

Abstract: Introduction: This paper presents the validation of a rapid method for the determination of nitrate content in chard samples, in order to determine, during two periods (winter and summer of 2012), the current levels of nitrate in this typical vegetable, and the toxicological risk associated with this intake. Material and Methods: A rapid colorimetric determination of nitrate in chard samples by nitration of salicylic acid was validated. The validated method was applied to analyze the content of nitrate in 56 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Croitoru et al (2015) reported that previous surveys showed that lettuce is a main source of nitrate, while monitoring data on retail samples detected nitrate and nitrite in spinach and lettuce; the details of which are summarized below (Iammarino et al, 2014). The nitrate concentrations in the leaves are higher than that of roots and fruits (Menal-Puey and Asensio, 2015). Influencing factors include the plant (e.g., variety, species, maturity) and the environment or season (e.g., temperature, humidity, light exposure, use of fertilizers or herbicides, water used, soil) (Iammarino et al, 2014;Croitoru et al, 2015;Menal-Puey and Asensio, 2015).…”
Section: Uptake In Leafy Vegetablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Croitoru et al (2015) reported that previous surveys showed that lettuce is a main source of nitrate, while monitoring data on retail samples detected nitrate and nitrite in spinach and lettuce; the details of which are summarized below (Iammarino et al, 2014). The nitrate concentrations in the leaves are higher than that of roots and fruits (Menal-Puey and Asensio, 2015). Influencing factors include the plant (e.g., variety, species, maturity) and the environment or season (e.g., temperature, humidity, light exposure, use of fertilizers or herbicides, water used, soil) (Iammarino et al, 2014;Croitoru et al, 2015;Menal-Puey and Asensio, 2015).…”
Section: Uptake In Leafy Vegetablesmentioning
confidence: 99%
“…The nitrate concentrations in the leaves are higher than that of roots and fruits (Menal-Puey and Asensio, 2015). Influencing factors include the plant (e.g., variety, species, maturity) and the environment or season (e.g., temperature, humidity, light exposure, use of fertilizers or herbicides, water used, soil) (Iammarino et al, 2014;Croitoru et al, 2015;Menal-Puey and Asensio, 2015). For instance, winter-grown leafy vegetables have been reported to have higher nitrate concentrations than summer-grown leafy vegetables (Menal-Puey and Asensio, 2015;Margenat et al, 2018).…”
Section: Uptake In Leafy Vegetablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparatively, most of these studies evaluated the content in chard, especially commercial samples. The content of nitrate observed in these studies varied from very low (<200 mg/kg) and low (200-500 mg/kg) to extremely high (>5000 mg/kg) [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Only the study carried out by Menal-Puey and Asensio [29] reported values in the range of medium (500-1000 mg/kg) and extremely high.…”
Section: Nitrate Content In Beta Vulgaris Varietiesmentioning
confidence: 99%
“…The content of nitrate observed in these studies varied from very low (<200 mg/kg) and low (200-500 mg/kg) to extremely high (>5000 mg/kg) [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Only the study carried out by Menal-Puey and Asensio [29] reported values in the range of medium (500-1000 mg/kg) and extremely high. Other interesting aspects of the recent studies presented in Table 1 are the influence of the fertilizing level, the season, the geographical area, and the production in the hydroponic system.…”
Section: Nitrate Content In Beta Vulgaris Varietiesmentioning
confidence: 99%